Preoperative Abdominal Computed Tomography at Rest and During Valsalva's Maneuver to Evaluate Incisional Hernias. (October 2019) - Bellio, Gabriele; Cipolat Mis, Tommaso; Del Giudice, Roberto; Munegato, Gabriele
Background . Incisional hernias (IHs) can develop in up to 15% of patients who underwent an abdominal surgical procedure. Abdominal computed tomography (CT) is the best examination to evaluate these patients before surgical repair. The aim of this study is to assess the usefulness of the abdominal CT scan during Valsalva's maneuver in patients who are candidates for surgery. Methods . A retrospective cohort analysis conducted on prospectively recorded data was performed on 26 consecutive patients affected by IHs who underwent a preoperative abdominal CT scan both at rest and during Valsalva's maneuver between January 1, 2015, and December 31, 2016. Results . Five patients (19%) had IH classified as M1-M2, 10 (39%) as M3, and 11 (42%) as M4-M5. Both the median IH orifice area (IHOA) and the median volume of the IH increased during straining ( P = .001 and P < .001, respectively). The percentage of the difference in volume ratios increased as the localization of the IH moved caudally. At the binary logistic regression analysis M3 IH, body mass index >28, IHOA > 156 cm 2 at rest, and IHOA > 138 cm 2 during Valsalva's maneuver were risk factors for posterior component separation. Conclusions . The preoperative CT scan both at rest and during Valsalva's maneuver seemed useful to estimate the risk of difficult IH repairs. Moreover, it could allow surgeons to decide if the patient should be addressed to more specialized centers.